The achaete‐scute complex in Diptera: patterns of noncoding sequence evolution. (7th September 2015) - Negre, B.; Simpson, P.
Abstract The achaete‐scute complex (AS‐C) has been a useful paradigm for the study of pattern formation and its evolution. achaete‐scute genes have duplicated and evolved distinct expression patterns during the evolution of cyclorraphous Diptera. Are the expression patterns in different species driven by conserved regulatory elements? If so, when did such regulatory elements arise? Here, we have sequenced most of the AS‐C of the fly Calliphora vicina (including the genes achaete, scute and lethal of scute) to compare noncoding sequences with known cis‐regulatory sequences in Drosophila. The organization of the complex is conserved with respect to Drosophila species. There are numerous small stretches of conserved noncoding sequence that, in spite of high sequence turnover, display binding sites for known transcription factors. Synteny of the blocks of conserved noncoding sequences is maintained suggesting not only conservation of the position of regulatory elements but also an origin prior to the divergence between these two species. We propose that some of these enhancers originated by duplication with their target genes.